Forms and functions of interrogatives in Lithuanian and Russian motherese - Balčiūnienė, Ingrida; Kazakovsk, Viktorija (Kalbotyra, 2011)
The paper focuses on adult interrogatives, which appear to be among the most frequent and typical ways of communicating with young children. The main objective of the investigation is to identify and compare the variety and distribution of interrogatives in Lithuanian and Russian motherese. The analysis is based on the data of a longitudinal observation of a Lithuanian girl Monika (2;0–2;8) and a Russian boy Vanja (2;0–2;8). The transcribed corpus of conversations between children and their parents was annotated for a multipurpose automatic linguistic analysis using tools of the program CHILDES (Child Language Data Exchange System, MacWhinney 1991). Despite several differences (the general number of questions, and the dominant forms of indirect correction), it can be stated that interrogatives in both Russian and Lithuanian motherese are generally used for the same conversational strategies; the communicative strategies in the two languages seem to be similar or even identical. Moreover, during the observation period, the conversational strategies in both Russian and Lithuanian motherese developed in a similar way. This calls for a general conclusion that a correlation between parental conversational strategy and the type of language can be identified.
Keywords: Lithuanian motherese; Russian motherese; conversational analysis; longitudinal study